I am falling in love, Ouch!: Ontological metaphors at work - Ni Gusti Ayu Roselani (Bina Nusantara University, 2020)
The research aimed to track the distribution of in metaphors and explore their ontological function in the abstracts of English research articles in the sub-disciplines of theoretical linguistics and pragmatics. The lack of empirical evidence on the subject had become the inspiration to base the research on a corpus. The corpus consisted of 40 research article abstracts; 20 from Journal of Linguistics and another 20 from Journal of Pragmatics. By using a quantitative method, the results show that theoretical linguistics abstracts are more densely populated with ‘in’ metaphors. However, in terms of in-preposition phrase topic complement variations, they are less varied. Qualitatively, the results confirm a notion proposed by Conceptual Metaphor Theory (CMT) that ‘in’ metaphors function cognitively by providing ontological status to abstract objects. Their existence proves to play an important role in academic texts.